Cumulative Damage in Very High/Low Cycle Combined Fatigue for TC21 Titanium Alloy - Baohua Nie; Shuai Liu; Yue Wu; Yu Song; Haiying Qi; Binqing Shi; Zihua Zhao; Dongchu Chen (Crystals, 2022)
The effect of low cycle fatigue (LCF) predamage with no precracks on very high cycle fatigue (VHCF) properties, and crack initiation characteristics for TC21 titanium alloy, was investigated. The results showed that LCF predamage with less than 5% of fatigue life had little influence on fatigue limit, but reduced its fatigue life. Fatigue cracks were initiated on the surface of the specimen at high stress amplitude, whereas fatigue cracks were initiated on the subsurface of the specimens at low stress amplitude. Based on Lemaitre damage theory, a very high/low cycle combined fatigue damage model was established to analyze the fatigue damage process, which was consistent with the experimental data. It was indicated that 5% LCF predamage value was the equivalent damage value, which was close to the critical value of VHCF crack initiation. The fatigue crack initiation of the specimens with LCF predamage less than 5% took up the major components of fatigue life.